(untitled) (Revista científica Olimpia, 2021)
The work had as objective the study of the education of the value industry in school with auditory limitations of fourth degree. They were applied in their development different methods of the theoretical level as they are analytic-synthetic, inductive - deductive; of the empiric level, the scientific observation and the interview. The focus of the study has present the transformation of the knowledge and the ways of the scholars’ of the value industry performance and it guarantees the participation of all the members of the sample in an interesting and varied way through the use of didactic materials, sport articles, stories, infantile songs from the class of education physics and he/she has as precept to the game in two fundamental moments, in one the physical abilities are developed in correspondence with the degree and in the other one the participation is promoted addressed to the invigoration of the shared value: industry.